Managerial roles and their application in non-profit sports organisations - Josef Voráček; Eva Čáslavová; Jiří Kraft (Karolinum Press, 2023)
This article focuses on leadership and the role of managers in the field of non-profit sports organisations, knowing that this area of activity is still largely neglected by research. The main goal of this research was to find out what roles managers currently play in the management of non-profit organisations in the field of sports. The method of a quantitative questionnaire survey was applied and the respondents were 270 non-profit sports organisation managers. The research shows that the roles of managers of non-profit sports organisations have significantly affected interpersonal activities to fulfil the mission of these organisations more than to strengthen their economic performance. The overshadowing of some managerial roles creates an incentive to focus on the creation of educational offers aimed at strengthening leadership, management of subsidies from public sources, and the possibility of using marketing in the field of creating their own financial resources.